Effect of Chinese Herbal Medicine Therapy on Risks of Overall, Diabetes-Related, and Cardiovascular Diseases-Related Mortalities in Taiwanese Patients With Hereditary Hemolytic Anemias - Chiu, Mu-Lin; Chiou, Jian-Shiun; Chen, Chao-Jung; Liang, Wen-Miin; Tsai, Fuu-Jen; Wu, Yang-Chang; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Chou, Chen-Hsing; Lin, Cheng-Wen; Li, Te-Mao; et al. (Frontiers in Pharmacology, 2022)
Hereditary Hemolytic Anemias (HHAs) are a rare but heterogeneous group of erythrocytic diseases, characterized by intrinsic cellular defects due to inherited genetic mutations. We investigated the efficacy of Chinese herbal medicine (CHM) in reducing the overall, diabetes-related, and cardiovascular diseases (CVDs)-related mortalities among patients with HHAs using a nationwide population database. In total, we identified 33,278 patients with HHAs and included 9,222 non-CHM and 9,222 CHM matched pairs after matching. The Cox proportional hazards model was used to compare the risk of mortality between non-CHM and CHM users. The Kaplan–Meier method and log-rank test were used to compare the cumulative incidence mortality between non-CHM and CHM users. The CHM prescription patterns were presented by the association rules and network analyses, respectively. The CHM prescription patterns were presented by the association rules and network analyses, respectively. CHM users showed significant reduced risks for of overall (adjusted hazard ratio [aHR]: 0.67, 95% confidence interval [CI]: 0.61–0.73, p < 0.001), diabetes-related (aHR: 0.57, 95% CI: 0.40–0.82, p < 0.001), and CVDs-related (aHR: 0.59, 95% CI: 0.49–0.72, p < 0.001) mortalities compared with non-CHM users. Two CHM clusters are frequently used to treat Taiwanese patients with HHAs. Cluster 1 is composed of six CHMs: Bei-Mu (BM; Fritillaria cirrhosa D.Don), Gan-Cao (GC; Glycyrrhiza uralensis Fisch.), Hai-Piao-Xiao (HPX; Endoconcha Sepiae), Jie-Geng (JG; Platycodon grandiflorus (Jacq.) A.DC.), Yu-Xing-Cao (YXC; Houttuynia cordata Thunb.), and Xin-Yi-Qing-Fei-Tang (XYQFT). Cluster 2 is composed of two CHMs, Dang-Gui (DG; Angelica sinensis (Oliv.) Diels) and Huang-Qi (HQi; Astragalus membranaceus (Fisch.) Bunge). Further randomized clinical trials are essential to evaluate the safety and effectiveness of above CHM products and to eliminate potential biases in the current retrospective study.